Matematică
sofi312
5

Rezolvati ecuatiile: a) 5x+3(x-6)=7x+13 b) 6x+4(x-8)=9x+21 c) 5(x-7)-2x=x-41 d) 7(x-9)-4x=x-39 e) 4(x+5)-3(x-3)=2(x+15) f) 5(x+2)-4(x-2)=3(x+8) g) 2[15+3(x-1)]=4(x+7) h) 2[4x-2)+16]=6(x+5)

+0
(2) Răspunsuri
marcugabriela52

a) 5x+3(x-6)=7x+13 5x+3x-18-7x-13=0 x-31=0 x=31 b) 6x+4(x-8)=9x+21 6x+4x-32-9x-21=0 x-53=0 x=53 c) 5(x-7)-2x=x-41 5x-35-2x-x+41=0 2x+6=0 2x=-6 x=-3 d) 7(x-9)-4x=x-39 7x-63-4x-x+39=0 2x-24=0 2x=24 x=12 e) 4(x+5)-3(x-3)=2(x+15) 4x+20-3x+9-2x-30=0 -x-1=0 -x=1 x=-1 f) 5(x+2)-4(x-2)=3(x+8) 5x+10-4x+8-3x-24=0 -2x-6=0 -2x=6 x=-3 g) 2[15+3(x-1)]=4(x+7) 2(15+3x-3)=4x+28 2(12+3x)-4x-28=0 24+6x-4x-28=0 2x-4=0 2x=4 x=2 h) ultima mai scrio odata ca nu inteleg cei cu parantezele

elenablonduta

a) 5x+3(x-6)=7x+13 5x+3x-18-7x-13=0 x-31=0 x=31 b) 6x+4(x-8)=9x+21 6x+4x-32-9x-21=0 x-53=0 x=53 c) 5(x-7)-2x=x-41 5x-35-2x-x+41=0 2x+6=0 2x=-6 x=-3 d) 7(x-9)-4x=x-39 7x-63-4x-x+39=0 2x-24=0 2x=24 x=12 e) 4(x+5)-3(x-3)=2(x+15) 4x+20-3x+9-2x-30=0 -x-1=0 -x=1 x=-1 f) 5(x+2)-4(x-2)=3(x+8) 5x+10-4x+8-3x-24=0 -2x-6=0 -2x=6 x=-3 atata stiu

Adaugă răspuns